Sejarah Pembentukan Soa Dan Perannya Dalam Sistem Pemerintahan Adat Di Negeri Tahalupu Kecamatan Waesala Kabupaten Seram Bagian Barat - Dokolamo, Hamid (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2021)
Countries in Maluku have a traditional government system known as customary government. The government was formed through a long process based on territorial genealogical principles so that the terms Matarumah, Petuanan, Soa, Badan Saniri Negeri and other government elements were known as part of customary institutions. So, as part of the customary government, it is a combination or union of one or several particular house or family elements. Referring to Law No. 5/1979, all Maluku villages whose status were states changed their names to desa. The uniformity of the governmental system in Indonesia has resulted in the loss of adat in Indonesian villages, including some as an element of government and an aspect of adat in Tahalupu. With the existence of the Law on regional autonomy and regional regulations of Maluku Province, which restore status villages to government institutions, research on the history of the formation of Soa and its role in the State of Tahalupu is essential to be studied scientifically so that it can be known and can be a reference and contribution to local history in Maluku.